2019
DOI: 10.15282/ijame.16.2.2019.4.0491
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of Eco-Friendly Crab Shell Powder Based Brake Pads for Automotive Applications

Abstract: The present study deals with the effective usage of crab shell, which is a solid waste in the seafood industry. The crab shell was powdered and treated with chemicals to obtain the chemically treated crab shell powder. The crab shell was powdered and heated to the desired conditions to obtain thermally processed crab shell powder. These two powders so obtained were used with other ingredients in the development of brake pads. For comparison crab shell powder free brake pads were also developed. The developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…When the figures are examined, it is seen that there are some adhering parts on the friction surfaces of the PBC containing pad with high friction coefficient. It is stated as abrasive wear in the literature [32][33][34]. This situation caused an increase in friction coefficient.…”
Section: Fig 2 Friction Coefficient-temperature Change Graph Of Pc0 Padmentioning
confidence: 99%
“…When the figures are examined, it is seen that there are some adhering parts on the friction surfaces of the PBC containing pad with high friction coefficient. It is stated as abrasive wear in the literature [32][33][34]. This situation caused an increase in friction coefficient.…”
Section: Fig 2 Friction Coefficient-temperature Change Graph Of Pc0 Padmentioning
confidence: 99%
“…Consequently, natural additives that are both environmentally friendly and can increase the braking performance of the pads have been the subject of many studies. [10] The heat generated during braking first affects the parts that are in contact (disc and brake shoe) and then dissipates into the environment through convection and radiation. The rate of this heat transfer is very important in terms of brake system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that the number of WSP-added friction coats contributed positively to the stability and wear resistance. Singaravelu et al [15] They investigated the effects of the powder obtained by chemical and thermal processing of crab shell powder on the performance of brake pads. Thermal stability was found using thermogravimetric analysis of brake pads.…”
Section: Introductionmentioning
confidence: 99%